ANALISIS SEBARAN JASA EKOSISTEM PENYEDIAAN PANGAN DAN AIR DI KABUPATEN KOLAKA UTARA - La Baco; hasbullah Syaf; Zulkarnain Zulkarnain; Albasri Albasri (Universitas Halu Oleo, 2019)
Ecosystem services for food and water supply are important to support regional economic development. The purpose of this research were to analyze the ability of ecosystems to provide food and water and its distribution spatially in North Kolaka District. This research was conducted through a study of ecoregion characteristics, including landscape characteristics, natural vegetation types and land cover. In addition, population data, water availability, food availability and administrative data in North Kolaka were collected. Data analysis includes the calculation of ecosystem service indexes, spatial distribution of ecosystem service indices and indicative status of the carrying capacity of food and water. The results showed that the average index of environmental services for food supply in North Kolaka District was 3.26 with a moderate category, while the index of environmental services for water supply was 2.77 with also a moderate category. Food service ecosystem service index in the medium category dominated North Kolaka District with an area of 214,119.36 hectares (72.96%) and a high category of 67,393.22 hectares (22.96%). The ecosystem services index of water supply is low and medium with an area of 58,429.52 hectares (19.91%) and 225,918.15 hectares (76.98%). The overall carrying capacity of food and water in North Kolaka District is still a surplus. The area of the food surplus reaches an area of 218,056.15 hectares (74.30%) and the total food surplus is 45,915,960,670 kcal. The area of water surplus in North Kolaka District is 230,914.85 hectares (78.68%) with a total surplus of 1,235,849,200 m3/year.Keywords: carrying capacity, ecoregion, ecosystem service index , spatial distribution